Faith Overcoming the World Based on 1 John 5:1-5 and Its Implications Among God’s Servants of the Indonesian Christian Congregation Surabaya - Noertjandranata, Handoko; Wahyuni, Sri; Sugiyarto, Kristian; Purwoko, Paulus (Technium Social Sciences Journal, 2023)
In 1 John 5:1-5, which discusses faith that is born of Elohim is that faith obtained from Yeshua is the Savior, and the apostle John writes that everyone believes that Yeshua is Hamashiakh, born of Elohim capable of conquering the world (Adeyemo, 2006). This expression is closely related to the background of the letter I John, namely the existence of problems regarding the presence of false teachers (I John 2:26), false prophets (I John 4:1), the antichrist (I John 2:18; 4 :3) which misled the congregation. This problem specifically occurs among God’s servants in the Surabaya municipality of the Indonesian Christian Congregation. Therefore, this research was conducted to determine the level of understanding of faith from God based on 1 John 5:1-5. To find the intended purpose, this research was conducted using quantitative research methods. The research results obtained are that the dominant background category determines Faith from God Based on 1 John 5:1-5 among God’s servants of the Indonesian Christian Congregation is age, this is different from the hypothesis proposed. The results of the analysis using Classification and regression trees (CRT) show that age background is the most dominant background category in forming Faith born from God Based on 1 John 5:1-5 among God’s servants of the Indonesian Christian Congregation Surabaya municipality (Y ). From the suragates table it is known that age background is able to improve by 14,216 points from the condition of Confirmation of Faith Born from God Based on I John 5:1-5 Among God’s Servants of the Indonesian Christian Congregation Surabaya Municipality (Y). Also from the importance table it is known that background age status was confirmed by 100% of respondents with a score of 17.659 points.